2013
DOI: 10.1371/journal.pone.0068302
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Airway Microbiota of Healthy Individuals and Patients with Chronic Obstructive Pulmonary Disease by T-RFLP and Clone Sequencing

Abstract: Chronic obstructive pulmonary disease (COPD) is a progressive, inflammatory lung disease that affects a large number of patients and has significant impact. One hallmark of the disease is the presence of bacteria in the lower airways. Objective: The aim of this study was to analyze the detailed structure of microbial communities found in the lungs of healthy individuals and patients with COPD. Nine COPD patients as compared and 9 healthy individuals underwent flexible bronchoscopy and BAL was performed. Bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 34 publications
4
70
1
1
Order By: Relevance
“…One hallmark of COPD is the increased susceptibility to colonization and infection by bacterial microorganisms (Sethi, 2010;Sethi and Murphy, 2008). Already in stable COPD, the microbiome of the lung differs from the microbiome of healthy individuals (Zakharkina et al, 2013). Specific bacterial species such as H. influenzae, M.catarrhalis, S. pneumonia, or P. aeruginosa are present in COPD lungs (Sethi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One hallmark of COPD is the increased susceptibility to colonization and infection by bacterial microorganisms (Sethi, 2010;Sethi and Murphy, 2008). Already in stable COPD, the microbiome of the lung differs from the microbiome of healthy individuals (Zakharkina et al, 2013). Specific bacterial species such as H. influenzae, M.catarrhalis, S. pneumonia, or P. aeruginosa are present in COPD lungs (Sethi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Lungs of COPD patients are often colonized or infected with Haemophilus influenzae, Moraxella catarrhalis, Streptococcus pneumonia, and Pseudomonas aeruginosa (Murphy et al, 2004;Sethi et al, 2006). Culture-independent approaches showed that the microbiome of the COPD lung differs significantly from the microbiome of healthy lungs (Erb-Downward et al, 2011;Sze et al, 2012;Zakharkina et al, 2013). The acquisition of a new bacterial strain during an AECOPD correlates with a more severe pulmonary neutrophilic inflammation and systemic inflammation (Sethi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using culture-independent techniques such as PCR amplification and sequencing of the 16S ribosomal (r)RNA gene have characterised a distinct bacterial community in the airway of COPD patients compared to healthy subjects and suggest that changes in the lung microbiota could be associated with enhanced airway inflammation and disease progression [8][9][10][11]. However, most lung microbiome studies to date have involved relatively small cohorts of subjects with limited longitudinal sampling and concurrent clinical information.…”
Section: Introductionmentioning
confidence: 99%
“…Previously considered sterile, breakthroughs in non-culture based detection methods have provided evidence that the respiratory tract harbors a microbiota (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Notably, the microbiota in the respiratory tract of healthy volunteers, smokers without COPD and patients with severe disease are distinct (9,10,(12)(13)(14). Though microbial dysbiosis has been shown to increase susceptibility to chronic diseases such as inflammatory bowel disease (IBD) (19,20), it is currently unknown whether such a phenomenon contributes to COPD.…”
Section: Introductionmentioning
confidence: 99%